Influencer, Media Sosial, dan Shopping Lifestyle terhadap Perilaku Impulsive Buying TikTok Shop Generasi Z Muslim - Pramesti, Putri Dian; Mubarok, Muhammad Husni (Institut Agama Islam Negeri Kudus, 2025)
AbstractThis study aims to examine the influence of influencers, social media utilization, and shopping lifestyle on impulsive buying among Muslim Generation Z consumers in Kudus City who use the TikTok Shop platform. A quantitative research approach was employed to address this objective. Data were collected through the distribution of questionnaires to respondents who met the predetermined criteria, and subsequently analyzed using multiple linear regression with the assistance of SPSS 26. The results indicate that the influencer variable does not have a significant effect on impulsive buying. A similar finding emerges for the social media usage variable, which likewise demonstrates no significant contribution to impulsive purchasing behavior. In contrast, the shopping lifestyle variable shows a significant effect and serves as a key factor explaining the tendency for spontaneous purchases among Generation Z. Furthermore, when tested simultaneously, all three independent variables exhibit a significant overall influence on impulsive buying, suggesting that the consumer behavior of Generation Z is shaped by a complex interaction between shopping lifestyle and digital engagement. These findings not only enhance the understanding of consumption patterns among Muslim Generation Z communities in Kudus but also provide practical implications for businesses, particularly in formulating more effective digital marketing strategies aligned with evolving consumer behavior in the social media era.Keywords: Influencer; Social Media; Shopping Lifestyle; Impulsive Buying; TikTok Shop. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh influencer, pemanfaatan media sosial, serta shopping lifestyle terhadap impulsive buying pada Generasi Z Muslim di Kota Kudus yang menggunakan layanan TikTok Shop. Dalam pelaksanaannya, penelitian ini mengadopsi pendekatan kuantitatif. Data dikumpulkan melalui penyebaran kuesioner kepada responden yang memenuhi kriteria penelitian, kemudian diolah menggunakan analisis regresi linear berganda dengan bantuan perangkat lunak SPSS 26. Hasil analisis menunjukkan bahwa variabel influencer tidak memiliki pengaruh yang signifikan terhadap impulsive buying. Temuan serupa juga terlihat pada variabel penggunaan media sosial yang tidak memberikan kontribusi signifikan terhadap perilaku pembelian impulsif. Namun demikian, shopping lifestyle terbukti memberikan pengaruh signifikan dan menjadi faktor yang mampu menjelaskan kecenderungan pembelian secara spontan di kalangan Generasi Z. Secara simultan, ketiga variabel independen tersebut terbukti memberikan pengaruh signifikan terhadap impulsive buying, sehingga menunjukkan bahwa perilaku konsumtif Generasi Z merupakan hasil dari interaksi kompleks antara gaya hidup belanja dan aktivitas digital. Temuan penelitian ini tidak hanya memperkaya pemahaman mengenai pola konsumsi Generasi Z Muslim di Kudus, tetapi juga menawarkan implikasi praktis bagi pelaku bisnis, khususnya dalam merancang strategi pemasaran digital yang lebih efektif dan responsif terhadap dinamika perilaku konsumen di era media sosial.Kata Kunci: Influencer; Sosial Media; Shopping Lifestyle; Pembelian Impulsif; TikTok Shop.